2010
DOI: 10.1200/jco.2009.26.4671
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Persistence With Oral Adjuvant Chemotherapy in Older Women With Early-Stage Breast Cancer in CALGB 49907: Adherence Companion Study 60104

Abstract: A B S T R A C T PurposePatient adherence is critical in evaluating the effectiveness of an oral therapy. We sought to measure adherence among women randomly assigned to capecitabine in a preplanned substudy of a multicenter clinical trial. Patients and MethodsCancer and Leukemia Group B study CALGB 49907 was a randomly assigned trial comparing standard chemotherapy versus oral chemotherapy with capecitabine in patients age 65 years or older with early-stage breast cancer. We used microelectronic monitoring sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
80
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 21 publications
8
80
2
3
Order By: Relevance
“…Larger group of patients with other types of cancer should be involved in the future to give more reliable information about this association. Cancer stage as well did not show any association with adherence score and this is supported by several previous studies (Partridge et al, 2010;Thivat et al, 2013;Verbrugghe et al, 2013).…”
Section: Adherence To Capecitabine Treatment and Contributing Factorssupporting
confidence: 85%
See 2 more Smart Citations
“…Larger group of patients with other types of cancer should be involved in the future to give more reliable information about this association. Cancer stage as well did not show any association with adherence score and this is supported by several previous studies (Partridge et al, 2010;Thivat et al, 2013;Verbrugghe et al, 2013).…”
Section: Adherence To Capecitabine Treatment and Contributing Factorssupporting
confidence: 85%
“…Parallel with earlier studies among capecitabine patients, patient adherence did not seem to be affected by the number of cycle (Partridge et al, 2010;Krolop et al, 2013;Thivat et al, 2013).…”
Section: Adherence To Capecitabine Treatment and Contributing Factorssupporting
confidence: 77%
See 1 more Smart Citation
“…Multiple studies regarding the adherence of patients to oral anticancer agents have been reported (1,2,(4)(5)(6)(7)(8). However, thus far, regimen adherence to tegafur/gimeracil/oteracil potassium (S-1) or capecitabine and multiple tyrosine kinase inhibitors have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies on medication compliance in oncology have focused on oral hormonal therapies in breast cancer 5, 6, 11, 12, 13 even though oral drugs are also frequently used in other cancers 14, 15, 16, 17. In colon cancer, the oral 5‐fluorouracil prodrug known as capecitabine is a commonly prescribed component in a large number of systemic therapy regimens 18, 19, but it has received relatively little focus to date 20, 21, 22, 23. Patients prescribed capecitabine may be at risk of not filling the initial prescription (noninitiation), failing to take the medication as prescribed (nonadherence), or continuing with the drug only temporarily (early discontinuation or nonpersistence) 20, 22.…”
Section: Introductionmentioning
confidence: 99%